Lepidagathis boholensis, a new name of Philippine Acanthaceae - Liang, Yi-Shuo; Geng, Shian-Tsan; Evangelista, Luisito T.; Wang, Jenn-Che (Phytotaxa, 2016)
A new name, Lepidagathis boholensis nom. nov., is proposed to replace the later homonym L. stenophylla Merr. Furthermore, a lectotype is also designated for the name Lepidagathis boholensis Y.S.Liang, S.T.Geng, L.T.Evangelista & J.C.Wang.